The Role of Training in Improving the Performance of Village Apparatus in Bawodesolo Village, Gunungsitoli Idanoi District, Gunungsitoli City - Zebua, Virginia Chrismonita; Waruwu, Eliyunus; Mendrofa, Syah Abadi; Laia, Otanius; Halawa, Forman (ProBisnis : Jurnal Manajemen, 2024)
This study examines the vital role of training programs in enhancing the performance of village officials, with a focus on Bawodesolo Village in Gunungsitoli Idanoi District, Gunungsitoli City. Grounded in Law No. 6 of 2014 concerning Villages, emphasizing citizen participation, particularly through the Village Consultative Body (BPD), the research explores training's impact on village officials' performance. Despite challenges like budget constraints and limited resources, strategic planning and government support can improve training effectiveness. Through qualitative methods, the study highlights the need for curriculum development, qualified instructors, and community involvement. Through a qualitative approach, including interviews, documentation, and observation, this study elucidates the complexities surrounding the implementation and impact of training programs. It underscores the need for strategic planning, curriculum development, qualified instructors, and ongoing evaluation to maximize the benefits of training. Furthermore, the study highlights the importance of community participation, transparency, and accountability in ensuring the success of training initiatives. Findings affirm the significant contribution of training programs to public services, decision-making, and community development. Overcoming obstacles and enhancing support mechanisms make training a valuable investment in governance and service delivery at the village level.